Preservation and documentation of Intangible Cultural Heritage: The Strategic Role of the Library and Information Science Professionals in Sri Lanka - Navaneethakrishnan, S. (University Librarians’ Association (ULA) of Sri Lanka., 2013)
Abstract (406 words) The purpose of this research is to shed light on an area of librarianship which is not often talked about in Sri Lankan context i.e. Preservation and documentation of Intangible Cultural Heritage (ICH). ICH takes many forms. It may be expressed in a number of domains, including Oral traditions and expressions, Performing arts, Social practices, rituals and festive events, Knowledge and practice about nature, Traditional craftsmanship and etc. UNSCO stipulates that state parties are supposed to ‘take necessary measures to ensure the safeguarding of the ICH in its territory.” These measures include identification of the ICH heritage that exists in its territory, adoption of appropriate policies, and promotion of education and so on. Generally initiatives for safeguarding ICH might include identifying and documenting such heritage, research, preservation and etc. In fact, the first step in safeguarding the ICH in a multicultural developing country is to identify those expressions and manifestations that can be considered as ICH and making a record, or inventory, of them. In Sri Lankan context, it is true that an under - standing of the ICH of different communities helps with intercultural dialogue, and encourages mutual respect for other ways of life. The objective of this research is to emphasis the need of the Preservation and documentation of ICH and to identify the Strategic Role of the Library and Information Science Professionals in Sri Lanka in Preservation and documentation of ICH. Based on descriptive analysis of literatures and current responsibilities of LIS professionals in relation to Preservation and documentation of ICH in Sri Lanka, this study outlines the need of national awareness on this topic through the identified new roles of LIS professionals. This study reveals that Library and Information Science Professionals in Sri Lanka has to play a vital role in Preservation and documentation of ICH in Sri Lanka. They have to develop their skills to act as anthropologists, Reporters, anchors or interviewers, commentators and journalists. This study further emphasis to start the process of a national scheme for Preservation and documentation of ICH in Sri Lanka based on international recommendations under the guidance of National Library of Sri Lanka. Libraries have an obligation to preserve the ICH. They might be objects, practices, representations, expressions, knowledge or skills. Whatever shape they take, these things form part of an ICH, and this ICH requires active effort on our part as LIS professionals from Sri Lanka in order to safeguard them over the generations.
Keywords: Library Science; Preservation and documentation; Intangible Cultural Heritage; Sri Lanka